Effects of Human-Social Capital Congruence and Environmental Dynamism on Dynamic of Encouragement and Organizational Innovation in New Ventures - Lu, Yurong; Cai, Wendi; Bi, Xiaoliang (Frontiers in Psychology, 2022)
Although human capital and social capital can provide knowledge and social network for organizations, existing studies are inadequate to explore how the interaction between the two types of capital shapes organizational behaviors or organizational outcomes. The present study investigates whether the linkage of human capital to social capital was compensatory or complementary, and how they impact organizational innovation in consideration of the dynamic of encouragement. Using data from more than 200 technological new ventures in China, we analyze the associations among all the parameters through bootstrapping and response surface methods. The findings suggest that organizational innovation is stronger when human and social capital are congruent and that the dynamic of encouragement fully mediates the relationship between capital congruence and organizational innovation performance. Furthermore, environmental dynamism positively moderates the relationship between capital congruence and the dynamic of the environment, that is, the relationship is stronger for new ventures in high rather than low dynamic environments. Finally, the theoretical and managerial implications of this study are discussed.